Kajian Sosiolinguistik pada “Nama Orang” di Jawa Timur - Mochamad Faizal Mohtarom; Ika Nurhayani; Esti Junining (Universitas Negeri Medan, 2023)
This study aims to analyze the changes in the meaning of